Tree-ring stable isotopes from the European Alps reveal long-term summer drying over the Holocene - Arosio, Tito; Leuenberger, Markus; Nicolussi, Kurt; Esper, Jan; Krusic, Paul J; Bebchuk, Tatiana; Tegel, Willy; Hafner, Albert; Kirdyanov, Alexander; Schlüchter, Christian; Reinig, Frederick; Muschitiello, Francesco; et al. (Science advances, 2025)
Here, we use 7437 stable oxygen (δ18O) isotope ratios extracted from 192 living and relict Alpine trees to reconstruct trends and extremes in European summer hydroclimate from 8980 before the present to 2014 Common Era. Our continuous tree-ring δ18O record reveals a significant long-term drying trend over much of the Holocene (P < 0.001), which is in line with orbital forcing and independent evidence from proxy reconstructions and model simulations. Wetter conditions in the early-to-mid Holocene coincide with the African Humid Period, whereas the most severe summer droughts of the past 9000 years are found during the Little Ice Age in the 18th and 19th centuries Common Era. We suggest that much of Europe was not only warmer but also wetter during most of the preindustrial Holocene, which implies a close relationship between insolation changes and long-term hydroclimate trends that likely affected natural and societal systems across a wide range of spatiotemporal scales.